NEW APPROACH FOR TREATMENT OF CUTANEOUS LEISHNIANIASIS BY MAN NITOL - A.Kadir, Mohammed; A. Jaleel , Nidham; Al-Zaidaw , Karim A. K. (The Iraqi Journal of Veterinary Medicine, 2021)
The present study was carried outinHaWija District and surrounding villages. Three villages were chosen (Al-Kadhemia,Sader A1-Naher, A1-Ameniea). The high incidence rate of cutaneous leishmaniasis was during the Winter months (December 1996 to March 1997). The total positive cases were 227 ( 111 males and 116 females). The highest incidence rate was among childeren ﬁom 1-10 years old. Intralesional mannitol solution was shown to be more effective ( 93.89% ) than Hypertonic Sodium Chloride 7% (HSCS) ( 87.50% ) but almost identical to pentostam ( 96.20% ). Most of lesions were cured in ﬁrst and second injection, in all three treated groups but few of them needed the third injection. In all three treated groups, the scar was absent or minimum aﬁer healing. None of the control lesions cured-within 6-8 Weeks. It is concluded that 20% rnannitol is aneffective local method of treatment for acute cutaneous leishmaniasis. The efficacy of 20% of mannitol is identical to pentostam and greater than 7% “ HSCS”. i